2022
DOI: 10.1002/ptr.7347
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, synthesis, analytical methods, pharmacological activity, and pharmacokinetics of loganin: A comprehensive review

Abstract: Iridoid glycosides (IGs) are found in many medicinal and edible plants, such as Gardenia jasminoides, Cistanche tubulosa, Eucommia ulmoides, Rehmanniae Radix, Lonicera japonica, and Cornus officinalis. Loganin, an IG, is one of the main active ingredient of Cornus officinalis Sieb. et Zucc., which approved as a medicinal and edible plant in China. Loganin has been widely concerned due to its extensive pharmacological effects, including anti‐diabetic, antiinflammatory, neuroprotective, and anti‐tumor activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 152 publications
0
9
0
Order By: Relevance
“…Loganin is a natural molecule that has been shown to have neuroprotective effects (Zhang et al, 2022). Our previous studies firstly showed that loganin induced antidepressant-like effects in behavior despair model (Pan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loganin is a natural molecule that has been shown to have neuroprotective effects (Zhang et al, 2022). Our previous studies firstly showed that loganin induced antidepressant-like effects in behavior despair model (Pan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…et Zucc. Loganin has widely pharmacological effects, including anti-diabetic, antiinflammatory, and neuroprotective activities (Zhang et al, 2022). In addition, it is worth mentioning that Corni Fructus has a long history of application as food in many regions of China (Huang et al, 2018;Wang et al, 2022a), indicating its high safety.…”
Section: Introductionmentioning
confidence: 99%
“…3 Loganin is one active iridoid glycoside that is found in Corni fructus approved as a medicinal plant in China, which has extensive pharmacological effects, including anti-tumor, antiinflammatory, and neuroprotective activities. 4 Moreover, previous studies suggest that loganin could attenuate cell pyroptosis in high glucose-treated Schwann cells and chondrocytes of osteoarthritis mice. 5,6 In addition, emerging evidence reveals the protective effect of loganin on I/R injury of kidney.…”
Section: Introductionmentioning
confidence: 99%
“…The application of traditional Chinese medicine is promising in myocardial I/R injury, and the natural products have attracted attention of research 3 . Loganin is one active iridoid glycoside that is found in Corni fructus approved as a medicinal plant in China, which has extensive pharmacological effects, including anti‐tumor, anti‐inflammatory, and neuroprotective activities 4 . Moreover, previous studies suggest that loganin could attenuate cell pyroptosis in high glucose‐treated Schwann cells and chondrocytes of osteoarthritis mice 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…( Huang et al ., 2018 ). The beneficial effects of this herb, which has long been used to alleviate various pathological phenomena, have been shown to be due to the antioxidative activity of these glycosides ( Zhang et al ., 2022b ). Morroniside isolated from C. officinalis was first reported to be an antioxidant by Xu et al .…”
Section: Introductionmentioning
confidence: 99%